A molecular contribution to the controversial taxonomical status of some freshwater snails (Caenogastropoda: Rissooidea, Cochliopidae) from the Central Andes desert to Patagonia - Koch, Eduardo (2015)
For over 40 years malacologists have been discussing the taxonomical status of Heleobia species, an enigmatic genus from Cochliopidae family (Caenogastropoda: Rissooidea). As with other rissooidean families, the considerable character convergence and the paucity of anatomical synapomorphies has proved to be a problem in resolving cochliopid phylogenetic relations and establishing the validity of several nominal cochliopid species. Here we present a molecular contribution to solve the taxonomical status of one of the most abundant Southern South America cochliopid genera which has many endemic species. We report molecular evidence that supports three of the four Heleobia groups described for this region, the “australis”, “parchappii” and “piscium” groups. The fourth, the “hatcheri” group, belongs not to Heleobia but to a different genus which itself should not be considered as part of the family Cochliopidae but closely related to genus Potamolithus Pilsbry & Rush, 1896.